2022
DOI: 10.1007/s00167-022-07074-4
|View full text |Cite
|
Sign up to set email alerts
|

The German version of the KOOS-Child questionnaire (Knee injury and Osteoarthritis Outcome Score for children) shows a good to excellent internal consistency and a high test–retest reliability in children with knee problems

Abstract: Purpose The Knee Injury Osteoarthritis Outcome Score for children (KOOS-Child) is a self-administered, valid and reliable questionnaire for children and adolescents with knee disorders such as Osgood Schlatter disease, anterior knee pain, and patella dislocation. This study aimed to cross-culturally adapt the German version of the KOOS-Child questionnaire and test the reliability in two groups of children, one treated conservatively and the other surgically. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…It exhibited good test-retest reliability, as all ICCs were above 0.80 for all subscales. These findings are consistent with the validation results of the German and Egyptian versions of the scale [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It exhibited good test-retest reliability, as all ICCs were above 0.80 for all subscales. These findings are consistent with the validation results of the German and Egyptian versions of the scale [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…The Moroccan version of the KOOS-Child scale demonstrated excellent internal consistency, as all Cronbach's α values were greater than 0.90, except for the symptoms subscale (α = 0.470). This finding is consistent with validation results from the German version of the KOOS-Child scale, which reported a Cronbach's α value of 0.6 for the symptom subscale at T1 and 0.52 at T2 [ 28 ]. Similar results were observed in the French Canadian version, where Cronbach's α values for the symptom subscale were 0.622 in cases and 0.572 in the control group [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Reliability : Twenty-one studies 21 23 , 26 , 27 , 29 , 31 33 , 36 , 38 , 39 , 41 , 45 , 46 , 48 , 49 51 , 53 reported on the test–retest reliability of the instrument. Four studies reported no intraclass correlation coefficient (ICC) values or ICC values ranging below <0.7, thus demonstrating insufficient evidence on the quality of the test–retest reliability of the instrument.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a two-week gap provided a balance between allowing for any genuine changes in participants' experiences related to the measured constructs and maintaining their engagement and commitment to the study. Research suggests that a two-week period strikes a reasonable balance for assessing the reliability of measures, without introducing substantial changes in participants' cognitive or situational contexts [35][36][37]. This approach aligns with established practices in reliability testing and enhanced the robustness of the study findings.…”
Section: Participantsmentioning
confidence: 87%